The Personification and Simile Found in the Song All Too Well (10 Minutes Version) by Taylor Swift - Nafisa, Dinda; Herlyna, Herlyna; Marleni, Sri (e-Journal of Linguistics, 2024)
This study seeks to explore how Taylor Swift utilizes figurative language in her song "All Too Well (10 Minutes Version)," aiming to unveil the deeper meanings buried within the song's lyrics. The data was carefully collected and analyzed; employing a descriptive qualitative method. Among the several figurative language  used in the song, the study focuses on personification and simile. Through a comprehensive examination, it becomes clear that these literary devices serve as effective tools in conveying profound emotions such as loss, emptiness, and melancholy. Taylor Swift's adept use of personification breathes life into lifeless things, while her skillful application of simile allows for vivid comparisons that enrich the emotional depth of the narrative. By studying the intricate interaction between words and emotion, this study provides valuable insights into the artistry of Taylor Swift's songwriting. It highlights the diligent skill of her lyrics, offering a deeper understanding of the complexity and nuance that attach in her work. Ultimately, this study contributes to the broader discourse on the significance of figurative language in music, underscoring its role in shaping the listener's interpretation and emotional experience. Through a comprehensive analysis of All Too Well (10 Minutes Version) , this study illuminates the power of language to evoke profound emotional responses, showcasing the enduring impact of Talor Swift's lyrical talent.